Bedah Soal AKM Sebagai Upaya Meningkatkan Pemahaman Literasi Numerasi Peserta Didik - Septia, Adilla Dwi; Nisa, Amelia; Pertiwi, Deby Try Meliana; Jumali, Akhmad; Fauziyyah, Ana; Sumliyah, Sumliyah; Abidin, Zaenal (Institut Agama Islam Negeri Kerinci, 2025)
The Minimum Competency Assessment (AKM) is an essential component of the National Assessment policy aimed at measuring students' reading literacy and numeracy competencies in depth. However, many vocational high school (SMK) students are not yet familiar with the characteristics of AKM questions, which require critical thinking and contextual understanding. This community service program was conducted to help students at SMK Negeri 1 Cirebon understand the structure and patterns of AKM questions through a classical question-analysis approach. The activity took place in March 2025, using a participatory method involving 35 tenth-grade students from five different classes. Students worked individually on AKM-type questions, followed by group discussions and evaluations using the Quizizz platform. The results showed that students gained a better understanding of AKM contexts, were able to identify key information, and apply appropriate problem-solving strategies. Moreover, they showed high enthusiasm throughout the activity. This program demonstrated that classical question-analysis is an effective strategy for enhancing vocational students’ readiness for AKM.